Social networks, mobility, and HIV risk among women in the fishing communities of Lake Victoria - Sarah Nakamanya; Elialilia S. Okello; Zachary A. Kwena; Gertrude Nanyonjo; Ubaldo M. Bahemuka; Freddie M. Kibengo; Ali Ssetaala; Elizabeth A. Bukusi; Saidi Kapiga; Patricia E. Fast; Janet Seeley (BMC, 2022)
Abstract Background Population mobility is a demonstrated barrier to reducing HIV incidence. A clear understanding of social networks and their influence on mobility among women in the fishing communities of Lake Victoria may contribute to tailoring effective interventions that suit the needs of these mobile women. Methods A cross-sectional qualitative methods study was conducted to understand mobility patterns among women resident and or working in fishing communities of Lake Victoria in Kenya, Tanzania, and Uganda. The study was conducted in six fishing communities from March 2018 to June 2019. The communities were purposively selected, based on population size (1000 people or more) and HIV prevalence of > 15% among women aged 18 years or older who had lived in the fishing community for at least six months. In-depth interviews were conducted with 24 key informants and 72 women from the sites in the three countries. Questions focused on women's social networks and other factors that fuelled or facilitated women's mobility as well as challenges they faced due to mobility. Data analysis followed a thematic framework approach. Results Different social groupings/networks existed among women in the fishing communities of Lake Victoria. These included female sex workers, women fish processors/traders, women bar workers/owners, restaurant workers, and family networks. Networks encouraged mobility, supporting finding work opportunities, but also increased sexual risks through partner changes. The benefits of networks included information sharing, financial support, and group protection, especially against violence. Conclusion Social networks and groupings among women in the fishing communities of Lake Victoria could be useful in tailoring HIV prevention and HIV care interventions to suit the needs of these highly mobile populations.